Doublecortin Mutation in an Adolescent Male. (3rd May 2019) - Zare, Isabelle; Paul, Dustin; Moody, Shade
Doublecortin (DCX) mutations cause abnormal development of the DCX protein that normally aids in neuronal migration during fetal development. These mutations lead to lissencephaly, or the appearance of a "smooth brain, " which is varying levels of pachygyria or agyria in severe cases. Many genetic variants of the mutation have been identified, and an even greater range of phenotypic presentations have been described in the literature. The X-linked lissencephaly (DCX) mutation leads to an X-linked gender-dependent condition that causes subcortical heterotopia in females and lissencephaly in males. The authors report the case of a 13-year-old male who presented to our clinic for new-onset seizure disorder. He had a past medical history of developmental delay and features of autism spectrum disorder which was diagnosed at age 5 years at an outside clinic. Magnetic resonance imaging (MRI) brain at age 5 years showed pachygyria of the frontal and temporal lobes. After extensive genetic testing over the course of over a decade, the patient was found to have a de novo mutation in the DCX gene diagnosed via whole-exome sequencing. Specifically, he was found to have a mosaic mutation of the DCX gene as a c.30-31 deletion. His previous MRI findings were consistent with a diagnosis of X-linked sporadic lissencephaly sequence and included mainly a diffuse bilateral pachygyria (isolated lissencephaly sequence X chromosome). Thickening of the cortex and pachygyria or agyria are classic findings of lissencephaly, but do not help specify any mutation in the gene, of which there are over 70 possibilities. Our patient is unique in that most individuals with DCX mutation have infantile seizures, severe intellectual disability, orthopedic complications, and postnatal microcephaly, which our patient does not have.